Development of an automated vehicle stop system for cardiac emergencies - Tung T. Nguyen; Issey Takahashi; Takahiro Tanaka; Eijiro Takeuchi; Shinpei Kato; Tatsuya Suzuki; Hitoshi Kanamori; Yoshiki Ninomiya; Hirofumi Aoki (Advances in Science, Technology and Engineering Systems Journal, 2017)
This paper describes the concept and configuration of a novel automated safety vehicle stop system, and a future prospect of the study. Intrinsic sudden death may cause traffic accident since such accidents sometimes involve not only the driver but also other traffic users such as passengers and pedestrians. Cardiovascular disease (CVD) is considered as a serious driving risk factor. The pain and others effects of cardiac events degrade driver’s performance, and CVD causes ischemia brought by the CVD induces incapacity of driving. In the automated safety vehicle stop system, which our research group has developed, steer-sensors collects bio-signals and a camera captures the driver’s posture to monitor driver’s incapability. When the driver loses his or her driving capability, the system takes over the maneuver of the vehicle and automatically drives to a safety spot by observing the traffic environment. An emergency scenario was used to demonstrate the system verifying its potential.
Keywords: Vehicle safety; Cardiac emergency; Automated driving; Bio-signal